Seabirds shaped the expansion of pre-Inca society in Peru - Jacob L. Bongers; Emily B. P. Milton; Jo Osborn; Dorothée G. Drucker; Joshua R. Robinson; Beth K. Scaffidi (PLoS ONE, 2026)
This research investigates the influence of seabird guano on agriculture in the Chincha Valley of southern Peru through multi-isotopic, archaeological, and historical data. We conduct stable carbon, nitrogen, and sulfur analyses of 35 late pre-Hispanic maize ( Zea mays ) cobs and 11 seabirds from archaeological contexts spanning the late Formative period ( c . 200 BCE – 150 CE) to the Colonial period (1532–1825 CE). We report the strongest evidence yet for pre-Inca use of marine fertilizers in Chincha. Isotopic and radiocarbon data corroborate colonial-era records and regional avifauna iconography and assemblages, indicating that Indigenous communities fertilized maize with guano by at least 1250 CE. Maize δ 15 N values are consistent with archaeological studies on guano manuring in Chile, expanding the known geographical extent of this agricultural practice. Maize δ 34 S values overlap with experimental field data but are not enriched in 34 S, possibly reflecting various environmental and cultural variables. We suggest that seabird guano fertilization played an important role in the sociopolitical and economic expansion of the Chincha Kingdom, and its eventual relationship with the Inca Empire. Our findings carry significant implications for the broader Andes, nuancing understandings of agricultural production in coastal environments while drawing attention to marine fertilizers as a potentially widespread driving force of social change among pre-Hispanic societies.